2020
DOI: 10.1038/s41598-020-72749-2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-subject consistency of spontaneous eye blink rate in young women across the menstrual cycle

Abstract: The spontaneous eye blink rate (EBR) has been linked to different cognitive processes and neurobiological factors. It has also been proposed as a putative index for striatal dopaminergic function. While estradiol is well-known to increase dopamine levels through multiple mechanisms, no study up to date has investigated whether the EBR changes across the menstrual cycle. This question is imperative however, as women have sometimes been excluded from studies using the EBR due to potential effects of their hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
(120 reference statements)
0
4
1
Order By: Relevance
“…Repeatability was better with blink rates ≤ 10 blinks/min (CoR: ±5.4 blinks/min) but less reliable above 10 blinks/min (CoR: ±18.8 blinks/min) (supplementary data Table 3). Previous studies intending to report repeatability of blink rate do not provide a standard repeatability measure to enable comparison with the present findings [6,18,28,29]. These findings suggest that the wearable eye tracker is able to reliably measure blink rate within the normal ranges of spontaneous blinking.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Repeatability was better with blink rates ≤ 10 blinks/min (CoR: ±5.4 blinks/min) but less reliable above 10 blinks/min (CoR: ±18.8 blinks/min) (supplementary data Table 3). Previous studies intending to report repeatability of blink rate do not provide a standard repeatability measure to enable comparison with the present findings [6,18,28,29]. These findings suggest that the wearable eye tracker is able to reliably measure blink rate within the normal ranges of spontaneous blinking.…”
Section: Discussioncontrasting
confidence: 46%
“…The repeatability of recent and commonly used blink measurement methods has not been assessed. Repeated measurements of blink rate have been reported for electrophysiology methods (magnetic search coil technique and electro-oculography) [6,18,28], and for manual counting of blinks from eye video recording [29][30][31] conducted in a laboratory setting where participants' head position was fixed. However, none of these studies reported standard measures of repeatability [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies intending to report repeatability of blink rate do not provide a standard repeatability measure to enable comparison with the present findings. 6 , 18 , 29 , 30 These findings suggest that blink repeatability may be better during reading than conversation and walking. These results provide a basis on which to estimate sample size in future studies.…”
Section: Discussionmentioning
confidence: 88%
“…The repeatability of recent and commonly used blink measurement methods has not been assessed. Repeated measurements of blink rate have been reported for electrophysiology methods (magnetic search coil technique and electro-oculography), 6 , 18 , 29 and for manual counting of blinks from eye video recording 30 32 conducted in a laboratory setting where participants’ head position was fixed. However, none of these studies reported standard measures of repeatability.…”
mentioning
confidence: 99%
“…Descriptive analyses were carried out in relation to participants’ demographic, questionnaire, and Crab Foraging Task data. One outlier (3 SD > mean) was detected for EBR and was removed from all analyses (Cook’s D = .20); this outlier threshold of three standard deviation units from the mean has been used in previous EBR studies (Byrne et al, 2016; Doughty, 2019; Hidalgo-Lopez et al, 2020).…”
Section: Methodsmentioning
confidence: 99%